Alcohol Use among Students of “Bećo Bašić” Secondary School (Plav) - Čekić, Said (Medical Word, 2026)
Alcohol use during adolescence carries health and social risks. We aimed to describe consumption patterns and attitudes among students of “Bećo Bašić” Secondary School (Plav) and to identify prevention targets. Cross-sectional anonymous online survey (Google Forms), 3–8 March 2025; N=139 (47.5% male; 52.5% female; age 15–18). Descriptive statistics (percentages). Current alcohol use: 14.4%. First contact typically at 15–16 years. Drinking most often occurs with friends; 57.6% know a peer who regularly drinks. Most respondents deem peer drinking unacceptable (61.9%) and harmful to health (86.3%), while 38.1% have witnessed negative consequences. Although personal prevalence is modest, exposure to peer drinking and early initiation is notable. Prevention should focus on peer contexts, early education (15–16 years), school programs, and enforcement of sales restrictions to minors.